The Effect of Board of Directors Characteristics on Corporate Social Responsibility Practices - Lay, Jenny Altany Lestari; Purwatiningsih, Purwatiningsih (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to determine the influence of board size, board independence, board activities and board tenure on corporate social responsibility practices in companies included in the sensitive industry classification in Indonesia that adheres to the two-tier system. This study is quantitative research using panel data design and purposive sampling methods with secondary data. The samples in this study were obtained from 26 companies in sensitive industries listed on the Indonesia Stock Exchange from 2017 to 2023 and data processing was carried out using the Feasible Generalized Least Squares) method. The results show that boards with smaller numbers of members tend to encourage better CSR practices because they are more efficient and coordinated. On the other hand, the size of the board of commissioners, independence, frequency of meetings, and term of office do not have much effect, even the term of office of commissioners that is too long actually has a negative impact on CSR. The theoretical contribution of this study is to enrich the application of resource dependence theory. This research can be used as a consideration for company leaders and regulators in making strategies, policies and regulations related to CSR in Indonesia.